Transient Left-Sided Paralysis following Robotic-Assisted Laparoscopic Uteropexy - Jasmina Kurdija; Jan G. Jakobsson (Case Reports in Anesthesiology)
We describe a case report of a 47-year-old ASA 2 female patient who exhibits severe headache and hemineurology during awakening following robotic pelvic prolapse surgery. The symptoms resolved spontaneously during the first postoperative day. We could not find any explicit root cause. Robotic surgery associated adverse events are discussed.